Penerapan Pemasaran Bergerak dan Digital pada Usaha Siomay melalui Pelatihan dan Pendampingan di Surabaya - Sihotang, Ellen Theresia; Mukhlis, Iqbal Ramadhani; Murdiawati, Dewi (Jurnal Abdimas Ekonomi dan Bisnis, 2024)
The culinary business, as part of Micro, Small, and Medium Enterprises (MSMEs), has the potential to generate promising income. One such example is the production of snacks, specifically dumpling, in the form of siomay. Doyan Somay is a business that produce siomay in Surabaya, which has been established since 2018. However, the revenue from this business has not reached its full potential by the end of 2023. The marketing strategy employed is still simple, relying primarily on partnerships with business affilliates and regular customers. Given this situation, the aim of this Community Service activity is to optimize Doyan Somay’s revenue by implementing digital marketing strategies. The solution offered to the partner is the application of marketing strategies through social media and mobile marketing using e-commerce platforms. The method used includes training  and mentoring. The methodology is based on four main stages: preparation, implementation, evalution, and monitoring. This series of community service activities has had a positive impact on the partner, especially in increasing the active use of social media and e-commerce as marketing channels. Gradually, the partner’s revenue has shown an increase of approximately two to three percent per day.